2022
DOI: 10.3390/life13010102
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds: Potential Therapeutics for the Inhibition of Cartilage Matrix Degradation in Osteoarthritis

Abstract: Osteoarthritis (OA) is the most common degenerative joint disease characterized by enzymatic degradation of the cartilage extracellular matrix (ECM) causing joint pain and disability. There is no disease-modifying drug available for the treatment of OA. An ideal drug is expected to stop cartilage ECM degradation and restore the degenerated ECM. The ECM primarily contains type II collagen and aggrecan but also has minor quantities of other collagen fibers and proteoglycans. In OA joints, the components of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 167 publications
0
9
0
Order By: Relevance
“…Subsequently, the levels of ECM-related proteins were determined. GPX7 overexpression promoted the accumulation of the ECM components, aggrecan and collagen II, and reduced the levels of MMP13 and ADAMTS5, which are key enzymes involved in cartilage degradation ( 24 ). The experimental results indicated that GPX7 has the ability to regulate and inhibit the aforementioned pathogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the levels of ECM-related proteins were determined. GPX7 overexpression promoted the accumulation of the ECM components, aggrecan and collagen II, and reduced the levels of MMP13 and ADAMTS5, which are key enzymes involved in cartilage degradation ( 24 ). The experimental results indicated that GPX7 has the ability to regulate and inhibit the aforementioned pathogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β and TNF-α, produced by immune cells, especially mononuclear cells, as well as activated chondrocytes, synoviocytes, and osteoblasts, are among the mediators that are released mainly in the early stages of OA ( 24 ). They are known to control the inflammatory cascade, induce the synthesis of matrix metalloproteinases (MMPs), nitric oxide, prostaglandin E2 (PGE2) and IL-6, reduce the synthesis of the main components of the extracellular matrix (ECM), while inhibiting the anabolic activity of chondrocytes and reduce the production of type II collagen ( 25 ). Catabolic events involving IL-1β and TNF-α are mediated through the activation of NF-κB intracellular signaling cascades.…”
Section: Discussionmentioning
confidence: 99%
“…The canonical Wnt/β-catenin signalling is an another pathway up-regulated in joint trauma [ 45 ]. The maintenance of chondrocyte metabolic balance depends on baseline Wnt activity, while enhanced Wnt activity, as found in PTOA, can cause related extracellular matrix-degrading proteases to degrade cartilage matrix [ 46 ].…”
Section: Inflammatory Response In Articular Cartilage and Synovium In...mentioning
confidence: 99%